Impact of Diabetes and obesity on Human Fertility and Semen Quality - Mohsin Hussein Sheikh Mohammad; Edrees Mohammad Ameen (Zanco Journal of Pure and Applied Sciences, 2021)
The present study was done to assist the effect of obesity and diabetes on semen quality and fertility of adult males in Erbil city. For this purpose, one hundred twenty adult males were used in this study. The subjects were divided into four groups. The control group included 30 healthy males, the obese group included 30 males with BMI ≥ 30. The diabetes group included 30 males with diabetes mellitus type 2 (T2 DM)and obese and the diabetes group included 30 males with both BMI ≥ 30 and T2 DM. Semen analysis and sex hormones were determined to evaluate semen quality and fertility. The incidence of abnormal viscosity in patient groups is significantly higher than that of the control group. Semen volume, sperm concentration, normal morphology, total motility, and grade activity in the control group is significantly higher than that of the other 3 groups. Lower sex hormones LH, FSH, and testosterone were recorded in a group of obese with diabetes group. A lower concentration of the serum malondialdehyde (MDA) is recorded in the control group. Despite the decreasing of the semen volume, sperm concentration, normal morphology, and motility in the patient's groups, all these values are not threshold and within the normal ranges which were recommended by World Health Organization (WHO). In our results concluded that obesity and diabetes have a minor effect and not detrimental to the fertility of males.